Alterations in blood glucose and plasma glucagon concentrations during deep brain stimulation in the shell region of the nucleus accumbens in rats - Diepenbroek, Charlene; van der Plasse, Geoffrey; Eggels, Leslie; Rijnsburger, Merel; Feenstra, Matthijs; Kalsbeek, Andries; Denys, Damiaan; Fliers, Eric; Serlie, Mireille J.; la Fleur, Susanne E. (Frontiers in Neuroscience, 2013)
Deep brain stimulation (DBS) of the nucleus accumbens (NAc) is an effective therapy for obsessive compulsive disorder (OCD) and is currently under investigation as a treatment for eating disorders. DBS of this area is associated with altered food intake and pharmacological treatment of OCD is associated with the risk of developing type 2 diabetes. Therefore we examined if DBS of the NAc-shell (sNAc) influences glucose metabolism. Male Wistar rats were subjected to DBS, or sham stimulation, for a period of one hour. To assess the effects of stimulation on blood glucose and glucoregulatory hormones, blood samples were drawn before, during and after stimulation. Subsequently, all animals were used for quantitative assessment of Fos immunoreactivity in the lateral hypothalamic area (LHA) using computerized image analysis. DBS of the sNAc rapidly increased plasma concentrations of glucagon and glucose while sham stimulation and DBS outside the sNAc were ineffective. In addition, the increase in glucose was dependent on DBS intensity. In contrast, the DBS-induced increase in plasma corticosterone concentrations was independent of intensity and region, indicating that the observed DBS-induced metabolic changes were not due to corticosterone release. Stimulation of the sNAc with 200 μA increased Fos immunoreactivity in the LHA compared to sham or 100 μA stimulated animals. These data show that DBS of the sNAc alters glucose metabolism in a region- and intensity dependent manner in association with neuronal activation in the LHA. Moreover, these data illustrate the need to monitor changes in glucose metabolism during DBS-treatment of OCD patients.